2010
DOI: 10.3945/ajcn.2010.30112
|View full text |Cite
|
Sign up to set email alerts
|

Child adiposity and maternal feeding practices: a longitudinal analysis

Abstract: Background: Parental control has been hypothesized to cause weight gain in children by weakening self-regulatory processes. However, most studies that link control with weight have been cross-sectional, and therefore causation is uncertain. It remains possible that parental control is a response to child overweight rather than a cause. Objective: We investigated the direction of the association between parental feeding practices and children's adiposity in a longitudinal study. Design: Three subscales of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
191
8
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(238 citation statements)
references
References 27 publications
31
191
8
8
Order By: Relevance
“…High BFI during early infancy also increased the odds of mothers being especially careful to ensure that their 6-year-old child eats enough. Because maternal overcontrol of feeding practices and children' s lack of self-regulation of energy intake have been associated with childhood obesity, 2,[33][34][35] it is possible that 1 of the pathways linking breastfeeding and obesity involves behavioral mechanisms related to bottle feeding. It is important for health professionals to emphasize infant-led feeding and following infant appetite cues when advising new parents, particularly when parents are bottle feeding.…”
Section: Discussionmentioning
confidence: 99%
“…High BFI during early infancy also increased the odds of mothers being especially careful to ensure that their 6-year-old child eats enough. Because maternal overcontrol of feeding practices and children' s lack of self-regulation of energy intake have been associated with childhood obesity, 2,[33][34][35] it is possible that 1 of the pathways linking breastfeeding and obesity involves behavioral mechanisms related to bottle feeding. It is important for health professionals to emphasize infant-led feeding and following infant appetite cues when advising new parents, particularly when parents are bottle feeding.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some recent studies found that children' s weight status acts as an antecedent to parent's food-related restrictions. 36,37 Together, our and previous findings suggest that domain-specific parenting may be partly context driven, whereas more general parenting is a quite stable construct that typically influences child development, but not the reverse.…”
Section: Figurementioning
confidence: 91%
“…12,23 Thus, it is not clear whether food parenting practices impact child weight, child weight status impacts food parenting practices, or the relationship is reciprocal. 56,57 In longitudinal/intervention research, there are a number of key measurement considerations, including the need for measures that are developmentally appropriate, show stability over time (in the absence of intervention), and are sensitive to the effects of intervention. In addition, longitudinal studies need to control for the child's baseline weight status, because parents' food parenting practices may be in response to their weight perceptions of their child.…”
Section: Longitudinal Designmentioning
confidence: 99%